ANALISIS TERJEMAHAN KALIMAT DALAM SURAT SPONSOR COMPASS INTERNATIONAL FOUNDATION (KAJIAN IDEOLOGI, METODE, TEKNIK PENERJEMAHAN DAN KUALITASNYA) - Anastasia Inda Nugraheni; Nababan M.R.; Djatmika Djatmika (Universitas Sebelas Maret, 2016)
The aims of the study are to identify types of sentences in the CIF sponsor letters and the text function or translation purpose in target text; to describe the translation techniques, methods, and ideology in achieving the translation purpose; to identify the impact of the translation techniques, methods, and ideology applied to the translation quality in terms of the accuracy of the accuracy, acceptability and readability; and to assess the translation techniques, methods and ideology selected in achieving the translation purpose. This study is a descriptive, qualitative research and focused on a single case. Sources of the data were 10 pairs CIF sponsor letters and the informants who gave information about accuracy, acceptability and readability of translation. Techniques of collecting data were document analysis, queestionnaires and FGD. Purposive sampling was applied in this research. Findings of this research show the followings. The types of sentenses are declaratives,interrogatives, imperatives and exclamatives. The result shows 15 functions of illocutionary act. There are 14 kinds of translation techniques to overcome the translation problems, 13,67% tends to the source text and 86,33% tents to the target text. The translation methods tends to communicative translation method and free translation method with domestication ideology. The impact of the the application of those translation techniques, methods and ideology toward the quality of translation is satisfactory with the average score of 2,84. This value indicates the accuracy, acceptance and readability of this translation is satisfactory. Related with the purpose of translation, the translation in this research successed in achieving text function or translation purpose. Keywords: Translation, Translation technique, Translation method, Translation ideology, Translation quality